HOME SECURITYSYSTEM DEVELOPMENT USING MOTION SENSOR WITH ALARM OUTPUT BASED ON ARDUINO UNO - Rahman, Taufiq (JURNAL TEKNISI, 2025)
Abstract: The increasing number of home burglaries highlights the need for an effective and affordable residential security system. Conventional door locks are often inadequate to prevent unauthorized access, especially when the home is left unattended. This study aims to develop a motion-based indoor security system that enhances security through real-time alerts. The system was designed using a prototype method, combining an Arduino Uno microcontroller, a Passive Infrared (PIR) motion sensor, a buzzer, and a GSM module. When motion is detected within a 5-meter range, the PIR sensor activates the buzzer and simultaneously sends an alert message to the homeowner's mobile phone via the GSM module. The circuit was tested in stages, including validation of the power supply, sensor responsiveness, and overall system integration. The results showed that the system operated reliably, with accurate motion detection and timely alert responses. The study concluded that the proposed solution is effective, low-cost, and applicable to enhance indoor or home security in everyday life.Keywords: arduino; home security; prototype; PIR sensor. Abstract : Meningkatnya jumlah kasus pencurian rumah menyoroti perlunya sistem keamanan hunian yang efektif dan terjangkau. Kunci pintu konvensional seringkali tidak memadai untuk mencegah akses tanpa izin, terutama ketika rumah ditinggalkan tanpa pengawasan. Penelitian ini bertujuan untuk mengembangkan sistem keamanan ruangan berbasis gerakan yang meningkatkan keamanan melalui peringatan waktu nyata. Sistem ini dirancang menggunakan metode prototipe, menggabungkan mikrokontroler Arduino Uno, sensor gerak Inframerah Pasif (PIR), buzzer, dan modul GSM. Ketika gerakan terdeteksi dalam jarak 5 meter, sensor PIR mengaktifkan buzzer dan secara bersamaan mengirimkan pesan peringatan ke ponsel pemilik rumah melalui modul GSM. Rangkaian ini diuji secara bertahap, termasuk validasi catu daya, responsivitas sensor, dan integrasi sistem secara menyeluruh. Hasilnya menunjukkan bahwa sistem beroperasi dengan andal, dengan deteksi gerakan yang akurat dan respons peringatan yang tepat waktu. Penelitian ini menyimpulkan bahwa solusi yang diusulkan efektif, berbiaya rendah, dan dapat diterapkan untuk meningkatkan keamanan ruangan atau rumah dalam kehidupan sehari-hari.Keywords: arduino; keamanana rumah; prototype; PIR sensor